Socijalna topografija srednjovjekovnog Dubrovnika primjer posjeda obitelji Mençe u burgusu na prijelazu 13. u 14. stoljeće - Benyovsky Latin, Irena; Haničar Buljan, Ivana (2020)
U radu se donosi detaljan pregled nekretnina koje je u dubrovačkom burgusu posjedovala vlasteoska obitelj Mençe tijekom 13. i u prvoj polovici 14. stoljeća. Prati se međusobna povezanost obiteljske strukture jedne od najutjecajnijih obitelji toga razdoblja, urbanoga razvoja grada te političko-društvenih okolnosti. U radu je primijenjena metodologija istraživanja socijalne topografije u urbanoj povijesti.
The paper provides a detailed overview of the real estate owned by the Mençe family in the burgus of Dubrovnik during the 13th and the first half of the 14th century. In this period, this very branched noble family played a very important role in the social, economic, and political life of the city, as well as the formation of the burgus. The author genealogically follows the estates of all those for whom we have data on real estate in the preserved documents. The expansion of the family shows that marriage strategy was crucial, namely marrying wealthy girls, who brought significant valuable assets in dowry and even real estate in the late 13th century. Another relevant factor for strengthening the family was the number of male descendants, and in case of widowhood, noblemen sought to remarry to a young girl from a family of affiliate interests. These were regularly families that were in some kind of relations – economic, neighbourly, clan, or all three. One can only speculate that the division of land in the burgus, outside the old city walls, had (among other things) to do with the political affiliation of those who largely stayed in Pustijerna and later, with the expansion of the city to the north, moved to a new zone near Pile. During the researched period, the spatially and functionally diﬀerent suburbs of Dubrovnik – both new and old – were reshaped and unified to form a new city centre. This long and complex process was accompanied by the construction of city walls (in diﬀerent phases) and changing the old lines of communications in relation to the key points of the city. The transformation of the suburban area into an urban one included, in addition to creating new streets, the division of large blocks into plots for building houses, which resulted in a change in the relationship between the centre and the periphery, as well as the residential mobility of the population.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 114-121.
Sažetak ; Summary.
Keywords: Socijalna topografija -- Nekretnine; Obitelj Mençe; 13./14. st. -- Srednji vijek; Dubrovnik